Physical Activity as a Modulator of Intraocular Pressure: Relevance for Sport Participation and Eye Health - Jakubowska, Marta; Dziegciarczyk, Anna; Włodarczyk, Aleksandra; Wiater, Zuzanna; Brankowska, Karolina; Swoboda, Kamil; Domagała, Szymon; Olejnik, Michał; Kądziołka, Witold; Górka, Artur Piotr (Quality in Sport, 2026)
Glaucoma is the leading cause of irreversible blindness worldwide, with elevated intraocular pressure (IOP) representing the primary modifiable risk factor for disease progression. While pharmacological, laser, and surgical interventions remain the cornerstone of treatment, increasing attention has been directed toward non-pharmacological strategies, particularly physical activity. This review synthesizes current evidence regarding the effects of exercise on IOP, emphasizing underlying physiological mechanisms, intensity-dependent responses, and long-term adaptations. Aerobic exercise induces acute reductions in IOP through structural expansion of Schlemm’s canal, suppression of aqueous humor production via sympathetic activation, and osmotic fluid shifts associated with increased plasma osmolarity. The magnitude of IOP reduction appears dependent on exercise intensity, with moderate-to-high intensity aerobic activity demonstrating consistent hypotensive effects, whereas low-intensity activity may fall below a physiological activation threshold. Long-term conditioning produces sustained baseline reductions in IOP (approximately 2–4 mmHg) and improves ocular perfusion pressure (OPP), suggesting potential neuroprotective benefits. In contrast, high-resistance training, particularly when accompanied by the Valsalva maneuver, may induce transient IOP spikes. Overall, structured aerobic exercise emerges as a clinically meaningful, low-cost adjunct to conventional glaucoma management. However, exercise prescriptions should be individualized, particularly for patients with advanced disease. Further research is required to clarify long-term outcomes across glaucoma subtypes. Aim of study. The aim of this study is to investigate the relationship between various forms of physical activity and their effect on intraocular pressure, as well as to asses how patients with glaucoma may benefit from these findings.